The Hymn on Tiflis from the Warda Collection - Anton Pritula (The Kartvelologist - A Bilingual Peer-reviewed, Academic Journal of Georgian Studies, 2012)
The Warda, a hymn-collection, from the Syriac Renaissance period. In the liturgical literature of the Church of East (the so-called Nestorian) the Warda collection holds a special place. Even judging by the titles of the hymns many men of letters living from the 12th to the 16th century participated in its creation besides Giwargis Warda to whom most of the hymns are ascribed. Besides, the collection is meant for the liturgical performance on night services of the festival days and Sundays of all the liturgical year. These two peculiarities make it the main monument of East Syrian liturgical poetry. Its numerous copies are known in different collections of the world. Strophic hymns contained in the collection are still a part of the liturgy of the East Syrian Church. Altogether there is over 120 hymns in the collection, most of which are ascribed to Giwargis Warda whose name provides the name of the collection. Due to their content one can distinguish the hymns as: exegetic, hagiographic, apocryphal narratives, describing historical events and calamities, dedicated to other subjects (such as personal penitence). The number of existing manuscripts of this hymn-collection forms several dosens, which represent either a short or a full recension.